The ring size of monocyclic ET‐1 controls selectivity and signaling efficiency at both endothelin receptor subtypes. (3rd May 2021) - Wolf, Philipp; Beck‐Sickinger, Annette G.
Abstract : Cardiovascular diseases (CVDs) like hypertension are a major cause for death worldwide. In the cardiovascular tissue, the endothelin system—consisting of the receptor subtypes A (ETA R) and B (ETB R) and the mixed agonist endothelin 1 (ET‐1)—is a major key player in the regulation of vascular tone and blood pressure. Tight control of this system is required to maintain homeostasis; otherwise, the endothelin system can cause severe CVDs like pulmonary artery hypertension. The high sequence homology between both receptor subtypes limits the development of novel and selective ligands. Identification of small differences in receptor–ligand interactions and determination of selectivity constraints are crucial to fine‐tune ligand properties and subsequent signaling events. Here, we report on novel ET‐1 analogs and their detailed pharmacological characterization. We generated simplified ET‐1‐derived monocyclic peptides to provide an accessible synthesis route. By detailed in vitro characterization, we demonstrated that both G protein signaling and the subsequent arrestin recruitment of activated ETB R remain intact, whereas activation of the ETA R depends on the intramolecular ring size. Increasing of the intramolecular ring structure reduces activity at the ETA R and shifts the peptide toward ETB R selectivity. All ET‐1 analogs displayed efficient ETB R‐mediated signaling by G protein activation and arrestin 3 recruitment. Our study provides in‐depth characterization of the ET‐1/ETA R and ET‐1/ETB R interactions, which has the potential for future development of endothelin‐based drugs for CVD treatment. By identification of Lys 9 for selective labeling, novel analogs for peptide‐mediated shuttling by ET‐1 are proposed. Abstract : The high homology in the endothelin system limits the generation of receptor‐selective ligands. Using amino acid substitutions, we synthesized novel peptide ligands and identified possible attachment sites for fluorescent cargos. By assessing G protein signaling and arrestin recruitment, we demonstrate that the length of the intramolecular disulfide bridge allows discrimination between the ETA R and ETB R and leads to ETB R‐selective peptides.